FAKTOR- FAKTOR YANG MEMPENGARUHI PRAKTIK INCOME SMOOTHING - ALYA SHAFIRA RAMADHANI; APIT SUSANTI (E-Jurnal Akuntansi TSM, 2021)
This study aims to obtain empirical evidence on what factors can affect income smoothing practices. In this study, the independent variables used are company size, profitability, public ownership, managerial ownership, institutional ownership, debt to equity ratio, and company value. The object of this research is manufacturing company listed on the Indonesia stock exchange 2017-2019. There are 36 companies that meet the criteria using purposive sampling method. The research model used was regression binary logistic analysis using IBM SPSS Version 25. The results of the research show that firm size, profitability, public ownership, managerial ownership, institutional ownership, debt to equity ratio, and firm value have no influence on income smoothing.